The Psychosocial Aspects of Team Sports: The Individual Versus the Team (Baltic Journal of Sport and Health Sciences, 2018)
This text is a part of a longer elaboration concerning the humanistic bases of the theories of team sports. The notion“sports games” refers to team sports, which are most popular in our culture (in Poland): volleyball, basketball,football and handball.Team sports are a very interesting matter for the observation, how the integrated human teams function. Sport, as aconstituent of social life, is liable to the principles and rules, which are similar to the ones we may observe in ambientreality. Willing to explain and describe those phenomena, we should reach for the knowledge from the subject fieldof social sciences; in this case — concerning the collective behaviours.In this analysis I took into consideration the opinions about the functioning of human communities — the opinionsformulated by G. Le Bon (1996), W. McDougall (1920), S. Freud (2000) and selected conceptions from contemporaryAmerican psychology concerning the relations between the individual and the group. In this context I emphasized areflection about the necessity of proper stimulation, when the development of an individual is concerned, which meansthe change towards the individualization of training in team sports. The character of this text is strictly theoreticalbut it is also an attempt to accentuate the importance of the knowledge of a team’s morphology and the relationsbetween an individual and other members of a team for sports practice. This knowledge is a substantial (but usuallyunderrated) element of the trainer’s work.Keywords: team sports, collective behaviours, philosophy, psychology of sport, role of trainer, team building.